2018
DOI: 10.1111/jre.12619
|View full text |Cite
|
Sign up to set email alerts
|

Is dietary melatonin supplementation a viable adjunctive therapy for chronic periodontitis?—A randomized controlled clinical trial

Abstract: Background and Objective Melatonin is synthesized naturally by pineal gland and responsible for regulation of sleep/waking cycle. It showed appreciated anti‐inflammatory and antioxidant properties. The aim of this randomized clinical trial (RCT) was to assess the additive effect of melatonin supplementation in insomniac individuals with generalized chronic periodontitis (gCP) after scaling and root planing (SRP). Material and Methods Seventy‐four gCP patients with primary insomnia participated in this 6‐month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(101 citation statements)
references
References 30 publications
4
90
0
Order By: Relevance
“…Systemic MEL supplement (10 mg oral MEL capsule once daily before bedtime) administrated for 2 months for patients with insomnia, in conjunction with scaling and root planning (SRP) yield to significantly greater clinical attachment level gain and periodontal pocket depth reduction and also lower salivary tumor necrosis factoralpha levels comparing to placebo [30]. Favorable results on periodontal parameters have been also obtained after SRP with an adjunctive dose of MEL (2 mg a day for 4 weeks) and vitamin C (60 mg for females and 75 mg for males for 4 weeks) comparing to SRP alone [31].…”
Section: Resultsmentioning
confidence: 99%
“…Systemic MEL supplement (10 mg oral MEL capsule once daily before bedtime) administrated for 2 months for patients with insomnia, in conjunction with scaling and root planning (SRP) yield to significantly greater clinical attachment level gain and periodontal pocket depth reduction and also lower salivary tumor necrosis factoralpha levels comparing to placebo [30]. Favorable results on periodontal parameters have been also obtained after SRP with an adjunctive dose of MEL (2 mg a day for 4 weeks) and vitamin C (60 mg for females and 75 mg for males for 4 weeks) comparing to SRP alone [31].…”
Section: Resultsmentioning
confidence: 99%
“…El-Sharkawy et al ( 153 ) reported that a daily dietary supplement of 10 mg melatonin may be an effective complementary treatment for patients with insomnia with generalized chronic periodontitis, resulting in an improved CAL and sleep quality, as well as lower PD and salivary TNF-α levels. During the entire study period, the improvement in insomnia was maintained for up to 6 months without any rebound, even though the daily dietary melatonin supplement was administered for only 2 months.…”
Section: Periodontitismentioning
confidence: 99%
“…The majority of experiments used melatonin for 2-4 weeks. For clinical research, the most common route is by oral administration, with doses fluctuating between 1-10 mg/day ( 56 , 127 - 129 , 153 ). In addition, melatonin can be used locally in the form of 1% orabase cream for the treatment of periodontitis ( 137 , 138 ).…”
Section: Differential Effects Of Melatonin Administered At Variousmentioning
confidence: 99%
“…Melatonin has been reported to have significant beneficial effects in animal models of PDs (Virto et al, 2018). Until today, two RCTs have ascertained the usefulness of melatonin supplementation as a SRP adjuvant in PD (El-Sharkawy et al, 2018, Bazyar et al, 2018, and another RCT evaluated a melatonin-based topical formulation providing also positive results (Cutando et al, 2015).…”
Section: Natural Bioactive Compounds or Derivativesmentioning
confidence: 99%